Is Activation the Active Ingredient of Transdiagnostic Therapies? A Randomized Clinical Trial of Behavioral Activation, Acceptance and Commitment Therapy, and Transdiagnostic Cognitive-Behavioral Therapy for Emotional Disorders. Issue 1 (January 2023) - Fernández-Rodríguez, Concepción; Coto-Lesmes, Rocio; Martínez-Loredo, Victor; González-Fernández, Sonia; Cuesta, Marcelino
Studying the usefulness of contextual and cognitive transdiagnostic therapies calls for an analysis of both their differential efficacy and their specificity when acting on the transdiagnostic conditions on which they focus. This controlled trial compares the post-treatment and 3- and 6-month follow-up effects of Behavioral Activation (BA), Acceptance and Commitment Therapy (ACT) and Cognitive-Behavioral Transdiagnostic Therapy (TD-CBT) on emotional symptomatology, and analyses the role played by Experiential Avoidance, Cognitive Fusion, Activation and Emotion Regulation in the clinical change. One hundred twenty-eight patients who fulfilled diagnostic criteria for anxiety and/or depression (intention-to-treat sample) were randomly assigned to three experimental group-treatment conditions (BA, n  = 34; ACT, n  = 27; TD-CBT n  = 33) and one control group (WL, n  = 34). Ninety-nine (77.34%) completed the treatment (per-protocol sample). In the post-treatment, all therapies reduced anxiety and depression symptomatology. In the follow-ups, the reduction in emotional symptomatology was greater in the condition which produced greater and more prolonged effects on Activation. Activation appears to be the principal condition in modifying all the transdiagnostic patterns and BA was the most efficacious and specific treatment. The trial was registered at ClinicalTrials.gov NCT04117464. Raw data are available onlinehttp://dx.doi.org/10.17632/krj3w2hfsj.1 .